Taking the Heat or Shifting the Blame? Ethical Leadership in Political-Administrative Relations After Policy Failures. (2nd November 2019) - de Ruiter, Minou
Abstract : Ministers are faced with intense account-giving pressures when things go wrong under their watch. While ministers carry hierarchical responsibility for the behavior of their top administrators, ministers have incentive to shift blame and scapegoat them after policy failures. This is likely since political-administrative relations in most parliamentary systems have become more managerial. However, there is little empirical research regarding the formal and informal accountability rules that govern ministerial and administrative accountability after failures. This article compares two parliamentary systems with ministerial responsibility: the Australian State of New South Wales (NSW) and the Netherlands. NSW political-administrative relations have become more managerial than Dutch ones. The comparison highlights two important ethical constraints for ministers: (a) formal rules guiding political-administrative relations; and (b) informal norms regarding appropriate ministerial account-giving. While hierarchically oriented accountability rules and informal (parliamentary) norms buttress Dutch top administrators, these buttresses are less patent in the NSW case. Subsequently, while Dutch ministers have multiple times taken "sacrificial responsibility" for policy failures, NSW top administrators often have to front the media and have taken the fall for their ministers. To conclude, formal accountability rules and informal rules-in-use make ministers take the heat instead of shifting the blame.